Metastatic adenocarcinoma to the wrist presenting as Carpal Tunnel Syndrome : a report of an unsual cause. - Syed Waseem Ahmad, Sharifah Roohi; Samsudin, O. C.; Shukur, M. H.; Ibrahim, S. (Malaysian Orthopaedic Association, 2011)
Secondary metastases to the hand or rare, accounting for 0.1% of all metastases, and commonly involve bones. Soft tissue involvement is extremely unusual although it is significantly more common in carcinoma than sarcoma. Metastatic lesions of adenocarcinoma of the return to the liver, lung and vertebrae are well known. Here we report an unusual site of metastatic deposit of primary adenocarcinoma of the return to the soft tissues of the wrist causing carpal tunnel syndrome, which if correctly diagnosed earlier from the symptoms could have prevented an untimely amputation.